2-[(E)-4-Quinolylmethylideneamino]phenol - Yildirim, Sema Oeztuerk; Akkurt, Mehmet; Guemues, Mustafa Kemal; Canlica, Mevluede; Kaban, Seniz; McKee, Vickie (INT UNION CRYSTALLOGRAPHY, 2008)
In the title compound, C16H12N2O, the dihedral angle between the two aromatic ring systems is 68.54 (5)degrees. The molecular packing is stabilized by intra- and intermolecular O-H center dot center dot center dot N and intramolecular C-H center dot center dot center dot N hydrogen-bond interactions.
Keywords: Crystallography